A Ricardian analysis of the impact of climate change on European agriculture - Steven Van Passel; Emanuele Massetti; Robert Mendelsohn (Fondazione Eni Enrico Mattei (FEEM), 2012)
This research estimates the impact of climate on European agriculture using a continental scale Ricardian analysis. Data on climate, soil, geography and regional socio-economic characteristics were matched for 37 612 individual farms across the EU-15. Farmland values across Europe are sensitive to climate. Even with the adaptation captured by the Ricardian technique, farms in Southern Europe are predicted to suffer sizeable losses (8% -13% per degree Celsius) from warming. In contrast, agriculture in the rest of Europe is likely to see only mixed impacts. Increases (decreases) in rain will increase (decrease) average farm values by 3% per centiliter of precipitation. Aggregate impacts by 2100 vary depending on the climate model scenario from a loss of 8% in a mild scenario to a loss of 44% in a harsh scenario.
Keywords: Q54; Q51; Q15; 330; Ricardian Analysis; Climate Change; European Agriculture; Climate Change Economics; Ackerbau; Klimaveränderung; Makroökonomischer Einfluss; EU-Staaten